Dynamics of soil organic matter, bulk density and infiltration rate on mining reclamation land - Bakri Bakri; As’ad Syazili; Zhoen Pristoyo Tampubolon (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Post-mining land reclamation is carried out to restore the environmental functions of the land. Monoculture and multiculture planting patterns have different impacts on soil’s physical properties. This study aimed to determine the effects of analyzing soil organic matter, bulk density, and measuring soil infiltration rates in monoculture and multiculture planting patterns. The research used survey methods, data analysis through tabulation, and statistical techniques. The results indicated differences in soil physical properties between the two lands and among the variables. Mahayung land exhibited higher organic matter content (1.08%) compared to Banko land (0.66%). Additionally, the average infiltration rate in Mahayung land (3.02 cm/hour) was higher than in Banko land (2.56 cm/hour), and the bulk density in Mahayung land (1.40 g/cm³) was lower than in Banko land (1.62 g/cm³). Organic matter content influenced the infiltration rate by 70.69%, and affected bulk density by 49.39%. Finally, the different planting patterns affect soil physical properties, and the relationships among variables show significant results.